ChemInform Abstract: A General and Efficient Pd‐Catalyzed Rapid 2‐Fluoroethoxylation of Bromo‐Chalcones. Issue 39 (September 2016) - Rangarajan, T. M.; Devi, Kavita; Verma, Akhilesh K.; Singh, Rishi Pal; Singh, Raj Pal
Abstract: Two of six investigated ligands efficiently support the 2‐fluoroethoxylation of bromochalcones.